2017
DOI: 10.1016/j.chom.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Persistent KSHV Infection Increases EBV-Associated Tumor Formation In Vivo via Enhanced EBV Lytic Gene Expression

Abstract: The human tumor viruses Epstein-Barr virus (EBV) and Kaposi sarcoma-associated herpesvirus (KSHV) establish persistent infections in B cells. KSHV is linked to primary effusion lymphoma (PEL), and 90% of PELs also contain EBV. Studies on persistent KSHV infection in vivo and the role of EBV co-infection in PEL development have been hampered by the absence of small animal models. We developed mice reconstituted with human immune system components as a model for KSHV infection and find that EBV/KSHV dual infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(172 citation statements)
references
References 77 publications
7
163
1
1
Order By: Relevance
“…This was hypothesized to be due to the increased immunogenicity of latency III cells (26). Similarly, a recent study using a mouse model of EBV/KSHV co-infection, latency IIb cells were detected at a high frequency (16). The pathophysiological relevance of latency IIb therefore supports our study to define latency-distinguishing host markers.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This was hypothesized to be due to the increased immunogenicity of latency III cells (26). Similarly, a recent study using a mouse model of EBV/KSHV co-infection, latency IIb cells were detected at a high frequency (16). The pathophysiological relevance of latency IIb therefore supports our study to define latency-distinguishing host markers.…”
Section: Discussionsupporting
confidence: 53%
“…Staining patient biopsies has demonstrated heterogeneity at the single cell level where many cells may be EBNA2-positive but negative for LMP1 (14, 15). These cells are often quite common as recent studies in a mouse model of EBV and Kaposi Sarcoma Herpes Virus (KSHV) co-infection also identified a high frequency of EBNA2+/LMP1-cells (16). Due to the wide distribution of LMP1 expression within a latency III LCL population, this technique does not allow for distinguishing LMP1 low latency III LCLs from LMP1 low latency IIb cells.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that PIAS1, but not PIAS2/3/4 gene level is significantly lower in EBV and KSHV-dually positive cell lines derived from infected huNSG mice, which support higher EBV lytic gene expression, than that in EBV-only cell lines derived from huNSG mice, which have lower EBV lytic gene expression (Figure S1M) (McHugh et al, 2017). …”
Section: Resultsmentioning
confidence: 71%
“…In addition, we cannot exclude that there might be a direct or indirect interaction between the two viruses, in this case, of cooperative type. Data from in vitro 41,42 and humanised animal models 43 studies suggest that such interactions, both cooperative and competitive, do exist. We previously observed in HIVuninfected Ugandan mothers and children, that KSHV and EBV salivary loads were inversely correlated, particularly in KSHV shedders, 40 suggesting a direct or indirect negative interaction.…”
Section: Relationship Between Ebv and Kshv Infectionsmentioning
confidence: 99%